Pelatihan Budidaya Tanaman Hortikultura dengan Teknologi Budidaya Tanpa Tanah (Hidroponik) di SMK Muhammadiyah 2 Gresik - Lailiyah, Wharyanti Nur; Utami, Dwi Retnaningtyas; Rahim, Andi Rahmad; Suhaili, Suhaili; Nurjannah, Indah (LPPM ITB AAS Indonesia Surakarta, 2024)
Community knowledge, especially from the extended family of Muhammadiyah Vocational High School 2 Gresik regarding hydroponic cultivation as capital to overcome the problem of food independence. Cultivating plants using a hydroponic system is considered a very profitable alternative in the agricultural sector, considering the increasingly narrow agricultural land in Indonesia, especially at Muhammadiyah Vocational High School 2 Gresik. Based on an analysis of the hydroponic cultivation situation which is engaged in productive economic activities, which includes the type of horticultural plant cultivation (vegetables and fruit), teacher and student activities are carried out to support food independence and community welfare. This activity was very effectively implemented to restore the economic smoothness of the community, especially Teachers and Students of Muhammadiyah Vocational High School 2 Gresik. Therefore, this activity aims to increase the understanding of school principals, teachers, and students to develop hydroponic plant cultivation. The method used in implementing this Community Service activity is using discussion lectures and practices in cultivating fruit and vegetable horticulture plants which are carried out directly at Muhammadiyah Vocational High School 2 Gresik. This community service activity was carried out at Muhammadiyah Vocational High School 2 Gresik. This activity was carried out to mobilize the benefits of planting and consuming hydroponic fruit and vegetables. This community service activity will start in March-August 2024. The output targets that have been realized are fruit and vegetable plant nurseries, transplanting to NFT (Nutrient Film Technique) hydroponic installations, and plant care during plant development. Harvest activities will be carried out in mid-July 2023. This community service activity is fully supported by research from the PP Muhammadiyah Higher Education Council and funding from the Mu Research Grant Batch VII for 2023/2024.